Development and performance evaluation of La2O3 doped WC-10Co-4Cr coatings for enhanced biofouling and slurry abrasion resistance - Vikrant Singh; Mohit Vishnoi; N. Jeyaprakash; Syed Quadir Moinuddin; Anindita De; Anuj Bansal (Journal of Materials Research and Technology, 2025)
Tungsten carbide WC-based coatings are widely used for wear-resistant applications; however, enhancing their resistance to biofouling remains a critical challenge, especially in abrasive and microbial environments. This study investigates the influence of La2O3 doping on the microstructure, mechanical performance, and antifouling behaviour of WC-10Co-4Cr coatings. In the present study, WC-10Co-4Cr and 1.5 wt% La2O3 doped WC-10Co-4Cr coatings were successfully developed over SS410 steel using High-Pressure High-Velocity Oxy-Fuel (HP-HVOF) spraying. La2O3 addition refined the microstructure, reduced porosity, and enhanced splat bonding. The doped coating exhibited superior microhardness (1228 HV0.3), higher bond strength (78.7 MPa), and reduced surface roughness. Slurry abrasion testing revealed the lowest mass loss for La2O3 doped coating (6.38–17.11 mg), owing to its dense and hard structure. Furthermore, biofouling analysis confirmed excellent antibacterial performance of the doped coating against and Escherichia coli, attributed to enhanced hydrophobicity and antimicrobial action of La2O3. Overall, La2O3 doping significantly improved mechanical, wear, and biofouling resistance. These enhancements position the doped coating as a promising candidate for use in highly abrasive and biofouling-prone environments.